Illusio and overwork: playing the game in the accounting field. Issue 8 (19th October 2015) - Lupu, Ioana; Empson, Laura
Abstract : Purpose: – The purpose of this paper is to understand: how and why do experienced professionals, who perceive themselves as autonomous, comply with organizational pressures to overwork? Unlike previous studies of professionals and overwork, the authors focus on experienced professionals who have achieved relatively high status within their firms and the considerable economic rewards that go with it. Drawing on the little used Bourdieusian concept of illusio, which describes the phenomenon whereby individuals are "taken in and by the game" (Bourdieu and Wacquant, 1992), the authors help to explain the "autonomy paradox" in professional service firms. Design/methodology/approach: – This research is based on 36 semi-structured interviews primarily with experienced male and female accounting professionals in France. Findings: – The authors find that, in spite of their levels of experience, success, and seniority, these professionals describe themselves as feeling helpless and trapped, and experience bodily subjugation. The authors explain this in terms of individuals enhancing their social status, adopting the breadwinner role, and obtaining and retaining recognition. The authors suggest that this combination of factors cause professionals to be attracted to and captivated by the rewards that success within the accounting profession can confer. Originality/value: – As well as providing fresh insights into the autonomy paradox the authors seek to make four contributions to Bourdieusian scholarship in the professional field. First, the authors highlight the strong bodily component of overwork. Second, the authors raise questions about previous work on cynical distancing in this context. Third, the authors emphasize the significance of the pursuit of symbolic as well as economic capital. Finally, the authors argue that, while actors' habitus may be in a state of "permanent mutation", that mutability is in itself a sign that individuals are subject to illusio.